O2-S1.03 ABC for people with HIV: a longitudinal qualitative study of responses to sexual behaviour recommendations among people receiving antiretroviral therapy in Jinja, Uganda. (10th July 2011) - Allen, C; Mbonye, M; Seeley, J; Birungi, J; Wolff, B; Coutinho, A; Jaffar, S
Abstract : Background: People living with HIV (PLHIV) taking ART are increasingly involved in positive prevention" initiatives. These are generally oriented to promoting Abstinence, "Being faithful" (partner reduction) and condom use. Methods: We conducted a longitudinal qualitative study with PLHIV using ART, who were provided with adherence education and counselling support by a Ugandan non-governmental organisation, The AIDS Service Organisation (TASO). Participants were 40 people selected sequentially as they started ART, stratified by sex, ART delivery mode (clinic- or home-based), and HIV progression stage (early or advanced). At enrolment and 3, 6, 18 and 30 months, semi-structured interviews and home observation visits explored adherence and life changes. Results: At initiation of ART, participants agreed to follow TASO's positive-living (similar to ABC) recommendations. Initially poor health prevented sexual activity. As health improved, participants prioritised resuming economic production and support for their children. With further improvements, sexual desire resurfaced and people in relationships cemented these via sex. Married male participants were able to use condoms with their wives, but married female participants were unable to assure consistent condom use despite serostatus disclosure to their husbands. Several participants sought and some obtained HIV positive partners (serosorting) for emotional security, support in ART adherence, sexual fulfilment, avoidance of stigma and sometimes parenthood. Respondents used condoms in the early period of new relationships, but several did not disclose HIV status to partners at first. Male partners of female respondents stopped using condoms after a variable initial period. This contributed to continued non-disclosure, since the women feared violence or loss of economic security from disclosure. Conclusion: Positive prevention interventions continue to concentrate on behavioural outcomes and education and counselling approaches. Our findings show that, as ART leads to health improvements, gender norms, economic needs, sexual desires and a wish for "normalisation" of social roles and relationships increasingly influence sexual behaviour. Positive Health, Dignity and Prevention require combinations of appropriate biological, behavioural and structural interventions tailored to the economic and cultural milieu and informed by an appreciation of the human rights of PLHIV.